Relationship between ham composition and carcass composition in finishing swine - Johnston, M.E.; Nelssen, Jim L.; Goodband, Robert D.; Hines, Robert H.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The relationship between ham and carcass composition of 120 barrows with an average initial weight of 130 lb was used to develop prediction equations to determine carcass composition based on ham composition. Eighty pigs were slaughtered to determine total body and ham composition. The first half were slaughtered at 230 lb and the second half at 280 lb. Longissimus muscle area, backfat thickness, whole ham weight, and trimmed ham weight of each pig were recorded 24 h following slaughter. The right ham and the right side of each carcass were ground and analyzed for protein, lipid, moisture, and ash contents. A correlation analysis was conducted at each slaughter weight to determine the relationship between total carcass and ham composition. Based on the results of the correlation analysis, we determined that it would be beneficial to run a regression analysis to develop prediction equations for carcass protein, lipid, and moisture contents. The ash content of the carcass did not appear to be highly correlated to any of the variables tested and, thus, a prediction equation for total body ash was not formulated. Using a stepwise regression analysis, the following equations and correlation coefficients were developed to determine total carcass composition at a slaughter weight of 230 lb: 1) carcass moisture = .4019 + .3911 (ham moisture) - .5301 (ham lipid) (R2 = .73); 2) carcass lipid = .3325 - .3787 (ham moisture) + .7334 (ham lipid) (R2 = .75); and 3) carcass protein = .1985 + .6757 (ham protein) + .0914 (longissimus muscle area) (R2 = .49). For pigs fed to the heavier slaughter weight of 280 lb, the prediction equations were: 1) carcass moisture = 1.2852 - 1.0558 (ham lipid) - 5.5573 (ham ash) - .0165 (whole ham weight) (R2 = .54); 2) carcass lipid = -.1650 + 1.0089 (ham lipid) + .0085 (whole ham weight) (R2 = .74); and 3) carcass protein = .4528 + 2.6234 (ham moisture) - 1.8241 (ham lipid) - 10.4795 (ham ash) + .4690 (ham protein) (R2 = .86). These results indicate that ham composition can be used to predict total carcass composition.
Keywords: Swine; Body composition; Heavy weight; Carcass